Pricing of forward and futures contracts - CHOW, Ying-Foon (Institutional Knowledge at Singapore Management University, 2000)
There has long been substantial interest in understanding the relative pricing of forward and futures contracts. This has led to the development of two standard theories of forward and futures pricing, namely, the Cost-of-Carry and the Risk Premium (or Unbiased Expectations) hypotheses. These studies have modelled the relationship between spot and forward/futures prices either through a no-arbitrage condition or a general equilibrium setting. Relatively few studies in this area have considered the impact of stochastic trends in the data. With the emergence of non-stationarity and cointegration in recent years, more sophisticated models of futures/forward prices have been specified. This paper surveys the significant contributions made to the literature on the pricing of forward/futures contracts, and examines recent empirical studies pertaining to the estimation and testing of univariate and systems models of futures pricing.